Short sisal fiber reinforced recycled concrete block for one-way precast concrete slabs - Lima, Paulo R. L. (2018)
This work is dedicated to the assessment of the structural performance of a new lightweight block for one-way precast concrete slabs made of short sisal fiber reinforced concrete (SSFRC) containing natural and recycled aggregate. The influence of the sisal fibers and recycled aggregate on the physical and mechanical properties was assessed experimentally, with clear benefits of fiber reinforcement on the post-cracking flexural capacity, while the higher water absorption of recycled aggregates had favorable impact on the compressive strength mainly in the FRC. Flexural tests were carried out on SSFRC blocks, as well as on ceramic and expanded polystyrene (EPS) blocks used commercially. The SSFRC blocks presented higher load and deflection capacity with much more ductile behavior, and with a geometry favorable for the passage of infrastructures. Slab panels including SSFRC, ceramic and EPS blocks were tested under four point bending configuration to assess the benefits of the new SSFRC block in quasi-real slab conditions. The results of these tests demonstrated the best structural performance of the SSFRC blocks over the other considered commercial solutions, not only in terms of initial stiffness, but also for the load at serviceability limit deflection conditions (average increase of 23%) and yield initiation (average increase of 38%); The observed continuous crack pattern crossing the SSFRC blocks and the main precast RC beams demonstrated the potentialities of these blocks to contribute for the structural performance of this type of slabs. Material nonlinear finite element simulations were carried out to derive, by inverse analysis, the values of the fracture mode I parameters of SSFRC. This multidirectional smeared crack model was also used to simulate the behavior of the composite materials and the SSFRC blocks, and the obtained level of accuracy has demonstrated the adequacy of the adopted inverse analysis strategy. A Finally, a parametric study was carried out to preview the potentialities of these new SSFRC blocks for this structural application, having been verified that a SSFRC block of 12 mm thickness and 250 mm height, of about 10 kg, is capable of accomplishing the standard recommendations, constituting a competitive and efficient solution for this market segment.